Relationship between Perceived Severity and Compliance with COVID-19 Preventive Behavior among Pregnant Women - Annisa Nurrachmawati; Tanti Asrianti; Febry Lawrenche (EMBRIO: Jurnal Kebidanan, 2022)
Several risk groups, one of which is pregnant women are susceptible COVID-19. Pregnancy is known as a susceptible condition to COVID-19 infection because it could cause immunity decrease. Therefore, it is necessary to comply with COVID-19 preventive behavior. This study aims to analyze the relationship between perceived susceptibility, perceived severity, perceived obstacle, perceived benefit and self-efficacy with COVID-19 preventive behavior among pregnant women in the work area of Sempaja Community Health Center. This was an observational study with cross sectional design. Samples were selected using purposive sampling technique based on inclusion criteria of pregnant women who lived and registered in the determined work area and had gestational age of more than 12 weeks. There were 194 pregnant women involved as the study samples. Data were analyzed using the Spearman Rank Test. The bivariate analysis revealed that there was relationship between self-efficacy (p value of 0.000), perceived barrier (p value of 0.025), perceived benefit (p value of 0.000), and perceived severity (p value of 0.000) with compliance with COVID-19 preventive behavior. However, there was no relationship between perceived susceptibility and compliance with COVID-19 preventive behavior (p value of 0.287). It can be concluded that the better perception of pregnant women, the better compliance with COVID-19 preventive behavior. It is recommended to increase health promotion in order to keep compliance with COVID-19 preventive behavior.